Detachable Lip and Cheek Plumper for Rehabilitation of Facial Disfigurement - Nada Fathalla Abdelbagi; Ibrahim Ahmed Ismail; Fadia Awadalkreem; Mohammed Nasser Alhajj (Case Reports in Dentistry)
Background. Hemimaxillectomy of acquired palatal defects may predispose the patient to hypernasal speech, leakage of fluids into the nasal cavity, impaired masticatory function, and swallowing difficulties leading to a detrimental impact on the quality of life. Sequentially, it can also affect individual character and trust in social life, leading to social phobia and anxiety. This article presents prosthodontic management of a young male patient with deformation of the entire right half of the face due to surgical removal of odontogenic myxoma. It describes a method where the clinician utilized a simple, noninvasive, and cost-effective technique to cut the weight of the obturator and to attain aesthetics, utilizing a detachable lip and cheek plumper. Case Presentation. A 19-year-old male attended the Prosthodontic Clinics at Faculty of Dentistry, the University of Khartoum, eight months after the surgical removal of a tumor. The chief complaint was difficulty eating or drinking. Furthermore, he dropped out of school because of his facial deformity and his indistinct voice. Medical and dental history revealed surgical resection of the entire right half of the maxillary alveolar bone due to myxoma. Intraoral examination revealed a well-healed surgical defect in the maxillary right buccal vestibule creating an oroantral communication. A treatment plan was formulated, keeping the patient’s demand in mind. The decision was made to treat the patient with a maxillary obturator that would gain its support from the remaining teeth and tissues with a detachable cheek and lip plumper. The use of dental magnets as a means of attachment was elected. Conclusion. This article has described a simple, noninvasive, and cost-effective method to improve facial appearance in patients with hollow faces. The plumper prosthesis successfully improved the patient’s appearance to the extent that comfort and function would permit and encourage self-esteem.